PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMKN 7 PADANG - Anissa Retna Sari; Lidya Martha (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of leadership style, work motivation on teacher performance at SMKN 7 Padang. The sampling method using total sampling technique with a total of 66 respondents. The research data were collected from the results of multiple linear regression analysis and hypothesis testing with the help of the SPSS application. The results of this study indicate that leadership style has a positive and significant effect on teacher’s performance, and work motivation has a positive and significant effect on teacher’s performance